Etiologic diagnosis of nonsyndromic genetic hearing loss in adult vs pediatric populations - King, Peter J; Ouyang, Xiaomei; Du, Lilin; Yan, Denise; Angeli, Simon I; Liu, Xue Zhong (Otolaryngology-head and neck surgery, 2012)
Determine the diagnostic yield of a shared genetic testing algorithm in adult and pediatric populations with sensorineural hearing loss (SNHL) and recommend effective testing strategies to evaluate for genetic causes of deafness in patients presenting with idiopathic sensorineural hearing loss. Hospital-based cohort study. University of Miami outpatient otology clinics between 2001 and 2010. Two hundred twenty-one adult and 163 pediatric patients with nonsyndromic sensorineural hearing loss. Peripheral blood samples were screened for mutations in GJB2 and GJB6 and mitochondrial DNA mutations 1555A>G, 7444G>A, and 3243A>G. Audiometric data and family history were also collected. GJB2/GJB6-related deafness was diagnosed in 23 of 163 pediatric patients (14%) compared with only 3 of 221 adults (1%). All adults had a family history of hearing loss, and 2 patients noted deafness onset at birth. Nineteen GJB2 mutations were identified with 35delG the most common mutation. The 35delG homozygous state was the most common pathogenic genotype (54%). Mitochondrial DNA (mtDNA) mutations were found in 6 adult probands (3%). No mtDNA mutations were found in pediatric patients. Testing for common GJB2/GJB6 mutations in pediatric patients has considerable value in establishing an etiologic diagnosis for SNHL. Similar testing in adults is of very low yield except perhaps in cases of early-onset SNHL or strong family history. Mitochondrial DNA testing should be considered in adults with idiopathic SNHL.